Increased tooth brushing frequency is associated with reduced gingival pocket bacterial diversity in patients with intracranial aneurysms - Mikko J. Pyysalo; Pashupati P. Mishra; Kati Sundström; Terho Lehtimäki; Pekka J. Karhunen; Tanja Pessi (PeerJ, 2019)
Objectives The objective of this study was to investigate the association of tooth brushing frequency and bacterial communities of gingival crevicular fluid in patients subjected to preoperative dental examination prior to operative treatment for unruptured intracranial aneurysms. Methods Gingival crevicular fluid samples were taken from their deepest gingival pocket from a series of hospitalized neurosurgical patients undergoing preoperative dental screening (n = 60). The patients were asked whether they brushed their teeth two times a day, once a day, or less than every day. Total bacterial DNA was isolated and the V3–V4 region of the 16S rRNA gene was amplificated. Sequencing was performed with Illumina’s 16S metagenomic sequencing library preparation protocol and data were analyzed with QIIME (1.9.1) and R statistical software (3.3.2). Results Bacterial diversity (Chao1 index) in the crevicular fluid reduced along with reported tooth brushing frequency (p = 0.0002; R2 = 34%; p (adjusted with age and sex) = 0.09; R2 = 11%) showing that patients who reported brushing their teeth twice a day had the lowest bacterial diversity. According to the differential abundant analysis between the tooth brushing groups, tooth brushing associated with two phyla of fusobacteria [p = 0.0001; p = 0.0007], and one bacteroidetes (p = 0.004) by reducing their amounts. Conclusions Tooth brushing may reduce the gingival bacterial diversity and the abundance of periodontal bacteria maintaining oral health and preventing periodontitis, and thus it is highly recommended for neurosurgical patients.